Superior Rectus Recession for Heimann–Bielschowsky Phenomenon - Shruti Nishanth; Mohamed Abrar; R. L. Naveena; Nishanth Madhivanan; Nivean Madhivanan; Pratheebadevi Nivean (TNOA Journal of Ophthalmic Science and Research)
Heimann–Bielschowsky phenomenon (HBP) is an uncommon condition with a low-frequency, coarse, vertical nystagmoid movement that develops after long-standing profound vision loss in an eye. We report a case of HBP that resolved with superior rectus recession. A 20-year-old man presented to us with complaints of defective vision and inward deviation of right eye (RE) since childhood. On examination, he had an esotropia with HBP in his right eye. A RE- medical rectus recession of 5mm with lateral rectus resection of 7mm and superior rectus recession of 5mm was performed for this patient. Following surgery, he was orthophoric and HBP was aesthetically corrected. The authors conclude that Superior rectus recession procedure can be a treatment option for HBP with a good outcome.